Small lymphocytic lymphoma and lung malignancy coincidence in a male patient: a case report and literature review. Issue 9 (27th September 2021) - Kakos, Christos D; Geropoulos, Georgios; Loufopoulos, Ioannis; Martzivanou, Eirini; Nicolae, Robert; Khiroya, Reena; Panagiotopoulos, Nikolaos; Mitsos, Sofoklis
Abstract: Lung carcinoma management secondary to chronic lymphocytic leukemia could be quite challenging. We report a case of a 60-year-old male with several co-morbidities, who presented with shortness of breath and persistent cough. A chest imaging showed a right pleural effusion and complete white-out of the right chest cavity. A computed tomography scan revealed consolidation of the right upper lobe with a 6-cm lesion in hilum with complete occlusion of right lobe bronchus. The patient underwent a video-assisted thoracoscopic surgery, drainage of pleural effusion and pleural and lung biopsy. Talc pleurodesis as well as a flexible bronchoscopy of the endobronchial lesion was performed. Histopathological examination showed a small B-cell lymphoma of the right pleura and an invasive non-small cell carcinoma of the right lung. Dual neoplasms are challenging in terms of diagnosing, and they usually require a multidisciplinary team for the right treatment strategy, including surgery and chemotherapy.